Unveiling practical insights of eHealth implementation in Europe: a grey literature review on legal, ethical, financial, and technological (LEFT) considerations - Bente, B. E.; Beerlage-de Jong, N.; Verdaasdonk, R. M.; van Gemert-Pijnen, J. E. W. C. (Frontiers in Digital Health, 2025)
BackgroundThe implementation of eHealth technologies can improve healthcare efficiency, accessibility, and affordability. However, it involves complex legal, ethical, financial, and technological (LEFT) challenges that can impede success. While our previous scoping review identified barriers such as balancing compliance with innovation, funding gaps, and unclear business models, there remains a significant gap in understanding how these challenges manifest in real-world settings. This study uses grey literature to explore practical experiences and strategies in addressing LEFT challenges during eHealth implementation.ObjectiveThis study aims to explore real-world experiences and perspectives on the legal, ethical, financial, and technological (LEFT) challenges encountered during eHealth implementation.MethodsA grey literature review was conducted by querying databases BASE and Policy Commons, consulting expert references for relevant reports, and using snowball sampling to identify additional relevant grey literature.ResultsWhile the aim of this study was to explore practical experiences, the grey literature mainly reflects policy-level concerns, including strategic and regulatory challenges, with limited insight into how organizations navigate eHealth implementation in practice. Legal barriers include navigating complex regulatory frameworks, interpreting regulations, and concerns about data privacy. Facilitators focus on centralized governance and Europe's role in the global data market. Ethical barriers address inequalities in access, while facilitators emphasize patient autonomy, clear consent processes, and digital literacy. Financial barriers stem from inadequate funding structures and unclear financial requirements, with public-private partnerships as facilitators. Technological barriers revolve around interoperability issues due to national IT infrastructure limitations, with facilitators working to improve data exchange.ConclusionsThis study highlights a disconnect between the strategic focus of available grey literature and the need for actionable, practice-based insights. The limited presence of real-world implementation experiences underscores the necessity for more operational documentation to support stakeholders facing interrelated LEFT barriers. Key challenges include the need for actionable legal and ethical frameworks, clearer ethical discussions aligned with legal requirements, sustainable financial infrastructures, and enhanced stakeholder involvement to address interoperability challenges. These challenges require cross-sector investment in IT infrastructures, harmonized data standards, and stronger collaboration among stakeholders. Coordinated efforts across all LEFT domains are crucial for effective eHealth implementation.